Penguatan UMKM Guna Ketahanan Ekonomi di Desa Kalilembu Kecamatan Karangdadap Kabupaten Pekalongan - Ahmad Taufiq; Nurul Afiyah; Mohammad Syaifuddin; Aan Fadia Annur (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
By being dominated by young people. This UMKM is engaged in clothing. Some of them are produced from materials into ready-made clothes. Some of them become deliverymen or resellers by selling to markets outside the city, such as: Solo Market, Tegal Gubuk, Jakarta, Kudus, etc. From this income they meet their daily needs. It can be seen that the working method used is still very traditional. Especially for resellers who carry out transactions or buying and selling activities by going directly to the intended store. Of course, this method is greatly affected by the current corona outbreak, where there are certain cities that have imposed a lockdown policy. Many complained that the market was difficult to reach, threatened with closing activities because it invited too many crowds, and that their income had decreased. with a livelihood as UMKM actors and as UMKM workers, their income has decreased due to covid 19. Coupled with the lack of knowledge about the creative economy, the people of Kalilembu Village are stuck and have difficulty developing their business. as a form of maintaining the community's economic resilience, the solutions that can be given are as follows: 1) Socializing the creative economy to the younger generation, especially SMEs. 2) Conduct online buying and selling lessons through e-commerce. 3) Development of creativity from convection waste as an alternative to increase income. 3) Dissemination of educational content to young children